A Novel HAGE/WT1-ImmunoBody® Vaccine Combination Enhances Anti-Tumour Responses When Compared to Either Vaccine Alone - Almshayakhchi, Rukaia; Nagarajan, Divya; Vadakekolathu, Jayakumar; Guinn, Barbara-Ann; Reeder, Stephen; Brentville, Victoria; Metheringham, Rachael; Pockley, A. Graham; Durrant, Lindy; McArdle, Stephanie (Frontiers in Oncology, 2021)
Many cancers, including myeloid leukaemia express the cancer testis antigen (CTA) DDX43 (HAGE) and/or the oncogene Wilms' tumour (WT1). Here we demonstrate that HAGE/WT1-ImmunoBody® vaccines derived T-cells can kill ex-vivo human CML cell lines expressing these antigens and significantly delay B16/HHDII+/DR1+/HAGE+/WT1+ tumour growth in the HHDII/DR1 mice and prolonged mouse survival in the prophylactic setting in comparison to non-immunised control mice. We show that immunisation of HHDII/DR1 mice with HAGE- and WT1-ImmunoBody® DNA vaccines in a prime-boost regime in two different flanks induce significant IFN- release by splenocytes from treated mice, and a significant level of cytotoxicity against tumour targets expressing HAGE/WT1 in vitro. More importantly, the combined HAGE/WT1 ImmunoBody® vaccine significantly delayed tumour growth in the B16/HHDII+/DR1+/HAGE+/WT1+ tumour model and prolonged mouse survival in the prophylactic setting in comparison to non-immunised control mice. Overall, this work demonstrates that combining both HAGE- and WT1-ImmunoBody® into a single vaccine is better than either vaccine alone. This combination vaccine could be given to patients whose cancer expresses HAGE and WT1 in parallel with existing therapies in order to decrease the chance of disease progression and relapse.